Inhibition of influenza virus in vivo by siRNA delivered using ABA triblock copolymer synthesized by reversible addition-fragmentation chain-transfer polymerization. (August 2014) - Hinton, Tracey M; Challagulla, Arjun; Stewart, Cameron R; Guerrero-Sanchez, Carlos; Grusche, Felix A; Shi, Shuning; Bean, Andrew G; Monaghan, Paul; Gunatillake, Pathiraja A; Thang, San H; Tizard, Mark L
Aim: Influenza virus remains a major threat, with outbreaks continuing to occur. Few treatment options are available and drug resistance can emerge rapidly. New drugs that can quickly be adapted to virus mutations are needed. Several highly effective siRNAs targeting influenza that inhibit virus replication are known; however, effective delivery of these siRNAs remains a challenge. The aim of this study was to demonstrate the safety and efficacy of ABA triblock copolymer-delivered siRNA to inhibit influenza virus replication in vivo .Materials & methods: We report on the delivery of a siRNA targeting the influenza virus in chicken embryos using an ABA triblock copolymer prepared by reversible addition-fragmentation chain-transfer polymerization, containing a central cationic block and two outer hydrophilic polyethylene glycol blocks.Results: A significant reduction of virus titer was observed with the polymer/anti-influenza siRNA complexes, whereas the control with polymer/control siRNA complexes showed no effect.Conclusion: These data suggest that a reversible addition-fragmentation chain transfer-based siRNA delivery platform may be suitable for combating infectious diseases in vivo . Original submitted 21 December 2012; Revised submitted 10 May 2013